Răspuns :
a= 9x2^100 - 2^99 x 5 - 3x 2^101=
=2^99(9x2-5-3x2^2)=
=2^99(18-5-12)=
=2^99 =
=(2^3)^33
b= 5x3^67-3^68-5 x 3^66 =
=3^66(5x3-3^2-5)=
=3^66(15-9-5)=
=3^66=
=(3^2)^33
b>a
=2^99(9x2-5-3x2^2)=
=2^99(18-5-12)=
=2^99 =
=(2^3)^33
b= 5x3^67-3^68-5 x 3^66 =
=3^66(5x3-3^2-5)=
=3^66(15-9-5)=
=3^66=
=(3^2)^33
b>a
a = 9 · 2¹⁰⁰ - 2⁹⁹ · 5 - 3 · 2¹⁰¹
a = 2⁹⁹ · (9 · 2¹ - 5 - 3 · 2²)
a = 2⁹⁹ · (9 · 2 - 5 - 3 · 4)
a = 2⁹⁹ · (18 - 5 - 12)
a = 2⁹⁹ · 1
a = 2⁹⁹
b = 5 · 3⁶⁷ - 3⁶⁸ - 5 ·3⁶⁶
b = 3⁶⁶ · (5 · 3¹ - 3² - 5 · 1)
b = 3⁶⁶ · (5 · 3 - 9 - 5 · 1)
b = 3⁶⁶ · (15 - 9 - 5)
b = 3⁶⁶ · 1
b = 3⁶⁶
a = 2⁹⁹ este mai mic decât b = 3⁶⁶
a = 2⁹⁹ · (9 · 2¹ - 5 - 3 · 2²)
a = 2⁹⁹ · (9 · 2 - 5 - 3 · 4)
a = 2⁹⁹ · (18 - 5 - 12)
a = 2⁹⁹ · 1
a = 2⁹⁹
b = 5 · 3⁶⁷ - 3⁶⁸ - 5 ·3⁶⁶
b = 3⁶⁶ · (5 · 3¹ - 3² - 5 · 1)
b = 3⁶⁶ · (5 · 3 - 9 - 5 · 1)
b = 3⁶⁶ · (15 - 9 - 5)
b = 3⁶⁶ · 1
b = 3⁶⁶
a = 2⁹⁹ este mai mic decât b = 3⁶⁶